DEVELOPMENT OF SMART POWER MANAGEMENT CIRCUIT FOR INTEGRATION WITH ENERGY HARVESTER DEVICE - GANESAN, MUNIANDY GOUNDER (IRC, 2019)
Multiple input energy harvesters which integrates with Power Management Circuit is developed in this project to gain a higher output voltage to power up any low-powered electronic devices. Power Management Circuit which is also known as PMC need to be designed to accept multiple inputs from various energy harvesters. The energy harvesters that used in this project are piezoelectric and electrostatic. The PMC consists of two MOSFETs which acts as a high frequency amplifier, a pulse voltage source switch which connects both energy harvesters, a full wave bridge rectifier to convert Alternating Current (AC) into Direct Current (DC), then a buck boost converter which is the combination of resistor, inductor (L) and Capacitor (C), Schottky diode for a low forward voltage and fast switching. Finally, the output energy produced will be stored in a supercapacitor. In this project simulation, characterization on the circuit results an improvement on final output voltage from the PMC. Trapping an input frequency of 50 Hz from piezoelectric and electrostatic energy harvesters produced a highest output voltage of 1.15V. Thus, the characterization of circuits proves that the multiple energy harvester could provide higher output voltage to the load compares to standalone transducers. At the end of this project any low power sensor device will be able to be power by an efficient PMC circuit.